Comprehending scientific metaphors in the bilingual brain: Evidence from event-related potentials - Shen, Lexian; Li, Xiaoguang; Huang, Shaojuan; Huang, Yanhong; Gao, Xinyu; You, Ziqing; Mao, Zirun; Tang, Xuemei (Frontiers in Psychology, 2022)
Using event-related potentials (ERPs), this paper investigates the way in which scientific metaphors are electrophysiologically processed in Chinese (L1) and English (L2), with the aim of investigating the different mechanisms for understanding metaphorical language in first (L1) and second (L2) languages. By time-locking the N400 and later LPC time windows, the research show how meaning integration differs between L1 and L2 at different stages when comprehending figurative language. We found that compared with Chinese scientific metaphors, English scientific metaphors elicited greater N400, smaller LPC (Late Positive Component), and greater late negativity, and English literals elicited greater late negativity. Our findings suggest that the dynamics of processing figurative meaning in bilingual brains over time show a complex pattern, with language, context, inference and salience jointly modulating temporal dynamics and possible cerebral asymmetries, supporting the revised hierarchical model.